Comparison in lipid parameters before and after L-thyroxine treatment in subclinical hypothyroidism according to the presence of thyroid peroxidase antibodies - Velkoska, Nakova Valentina; Krstevska, Brankica; Cheshlaroska, Markushoska Katerina; Jovanovska Mishevska, Sasha; Milenkovikj, Tatjana (Bioscientifica, 2022)
Objective: Subclinical hypothyroidism (ScH) is a common condition and may be associated with dyslipidemia. We investigated the effect of levothyroxine therapy (L-T4) on lipid parameters in patients with a mild form of subclinical hypothyroidism according to the presence of thyroid peroxidase antibodies (anti-TPO antibodies). Material and methods: Fifty-seven patients with newly diagnosed ScH (TSH levels between upper reference value and 10 mIU/l with normal FT4 and FT3 values) with indications for L-T4 therapy were included in the study. Lipid parameters and presence of anti-TPO antibodies were evaluated at the moment of diagnosis and after 6 months euthyroid stage. Results: Average value of TSH was 8.1 ±1.9 mIU/l. Thyroid substitution therapy significantly decreased total cholesterol and LDL-C, and increased HDL-C (5.6±0.9 vs. 5.3±1.1; 3.4±1.0 vs. 3.2±1.1; 1.5±0.5 vs. 1.6±0.5 mmol/l, P<0.05 respectively). Statistically significant decrease in total cholesterol, total cholesterol/HDL-C, and, LDL-C/HDL-C were observed in patients with positive anti-TPO antibodies after 6 months euthyroid state (5.5±1.1 vs 5.3± 0.9 mmol/l; 3.9±1.5 vs. 3.5±1.0; 2.5±1.2 vs. 2.2±0.8, P<0.5 respectively). There was not statistically significant differences in lipid profile in patients with negative anti-TPO antibodies before and after L-T4 treatment. Conclusion: The effect of the thyroid substitution therapy on lipid parameters was more pronounced in patients with mild ScH and positive thyroid antibodies. Patients with mild ScH and positive anti-TPO antibodies may benefit of L-T4 treatment even in the lower TSH values.